The Relationship Between Akidah Akhlak Teacher's Personality Competence and Moral Development of MAN Dairi Students - Maha, Linna; Nainggolan, Romauli; Kesumawati, Leni (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2024)
This research aims to determine the personality competency of moral belief teachers, student morals and the relationship between the personality competency of moral belief teachers and student morals at MAN Dairi. The population in this study was all class X students, totaling 214 students. Sampling was carried out using a random sampling technique of 40 students. This research was conducted qualitatively using a case study approach. Data collection was carried out using library research and field research using thorough observation and interview techniques with teachers in the Aqidah Akhlak field of study and questionnaires distributed to students. The results of this research indicate that the personality competence of the moral aqidah teacher has a positive and significant influence on the morale of MAN Dairi students